Introdução a programação a partir de conhecimentos sobre música - Blatt, Lucas (2019)
The computer has been considered an extremely attractive tool for musical education as well as for creating and manipulating sounds. Its accuracy, possibilities for new timbres and the potential for automation make it an attractive platform for experimentation in music making. But to a certain extent, we need to know to instruct it to perform and how to do it. Based on this, we need to learn how to program a computer. In the courses of programming languages, the difficulty that many students face while learning such subject, mostly because to master this skill as a whole, a great deal of abstraction and conceptual knowledge is necessary. The activities in the classroom and on the notebook or even on the desktop become uninteresting because they do not allow the student to visualize in the real world its output. In this way, a reference was made on programming teaching and meaningful learning, followed by the relationship between music and technology. From the action research, a teaching proposal was developed that was implemented with a group of music students, gathering the necessary information to verify the validity of the proposal, which aims to teach programming for musicians.